The language focus of Science education integrated with English learning - Piacentini, Valentina (2017)
Global education demands being directed to scientific literacy and language proficiency, research on the school integration of Science and English and on the language focus for Science education is highly relevant. One educational approach is CLIL, aiming both at learners’ Content and Language acquisition. The main objective of our work – framed in the socio-constructivism and designed as a case study – is to understand what teaching strategies and classroom interactions have been developed and can be promoted in the “English Plus” project in one Portuguese school to support students, when Science education is integrated with English use. Context characterization shows the importance of developing a language-aware teaching approach to improve the subject education and student learning. To foster that, an instrument has been constructed and is presented here.